Clarification of musk lime base on color - Sinnasamy, Thilageswari (2012)
Clarification of musk lime base on color can directly gain to marketing company because grading process must when it comes to exporting such materials.In the Malaysia,this type method of grading for musk lime is not used which cause imbalance in marketing as the price of the musk lime varies with the grade.Therefore,this system carried out to develop a prototype judging the musk lime maturity and to estimate the expiry date of musk lime by their color.Software development life cycle methodology was implemented in this system design by using several image processing techniques including image acquisition, image enhancement and feature extraction.Seventy four sample data of musk limes were collected during image acquisition phase in the format of RGB color image.The grading systems use a computer and capture the image of musk lime using wed cam.Then,it the background of the image removed by using averaging filtering techniques.Next,RGB color information is changed to HSV color information.The values are then being used as information for determining the maturity and estimate expiry date of musk lime.